Analisis Faktor-faktor yang Mempengaruhi Kepatuhan UMKM Cemilan Nana PKU dalam Menyusun Laporan Keuangan - Yolanda Arsita Putri; Syaharani Mutia Sinulingga; Naiya Aulia Putri; Evi Suryani; Rifqi Muzakki; Siti Rodiah (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
This research was conducted at the Nana Pku Snack MSMEs at the Jl. Tuanku Tambusai No.34 Pekanbaru branch. This study aims to provide education and how to implement good financial management to the Cemilan Nana Pku branch 2 MSMEs. The research method applied by researchers is Qualitative Descriptive Method, by conducting interviews and documentation. The results of the study found that the factors that influence the interest of MSMEs in preparing Financial Statements are the lack of understanding of MSME actors in recording Financial Statements and choosing to record very simple financial reports so that they have not followed the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM).